A proposed set of exercises on inference making designed for high school freshmen - Ellaga, Michaela Villamin 1928- (1977)
The exercises on this paper intended for high school freshmen were patterned after the Reading for Understanding series and were intended to give training in inferential skills. This study aimed further to provide teachers in the field with examples in the preparation of materials that would enhance the student's ability to comprehend implied ideas. Results of this study revealed that the students' reading level is much lower than their grade placement.
"March, 1977."
Vita.
Thesis (M.A,T. Reading)--University of the Philippines, Diliman.
Keywords: Reading (Secondary) -- Philippines -- Problems, exercises, etc; Reading comprehension -- Philippines -- Problems, exercises, etc